RESPON PEMBERIAN KOMPOS DAUN KELAPA SAWIT DAN NPK 16.16.16 TERHADAP PERTUMBUHAN SERTA PRODUKSI BAWANG MERAH (Allium ascalonicum L.) - Al Muzafri; Khusnu Abdillah Siregar; Lufita Nur Alfiah (SUNGKAI, 2022)
ABSTRACT Response to Composting Palm Leaves and NPK 16.16.16 in Improving Growth and Production of Shallots (Allium ascalonicum L.). The purpose of this study was to determine the interaction effect and the main growth and production of shallots given oil palm leaf compost and NPK 16.16.16. This research was carried out at the Experimental Garden of the Faculty of Agriculture, Pasir Pengaraian University, Rokan Hulu Regency. This research will be carried out for three months starting from October 2021 to December 2022. This study used a factorial completely randomized design (CRD) consisting of two factors. The first factor was the provision of Palm Leaves Compost (K) consisting of 4 levels and the second factor was NPK 16.16.16 (G) fertilizer which consisted of 4 levels so that 16 treatment combinations were obtained with 3 replications, so there were 48 experimental units. Each unit consisted of 6 plants per plot and all plants were observed as samples so that the total plants were 288 plants. The parameters observed were the relative growth rate of plants, plant height, harvest age, number of tubers per clump, wet weight per clump, dry weight per clump, and tuber weight loss. The data were statistically analyzed and presented with the Honest Significant Difference Test (BNJ) at the 5% level. The results of the study can be concluded as follows: The interaction of oil palm leaf compost and NPK 16.16.16 fertilizer had a significant effect on: plant height, harvest age, number of tubers per clump, wet weight of tubers per clump, dry weight of tubers per clump and tuber weight loss. The best treatment was a combination of oil palm leaf compost treatment of 45 grams/polybag (K3) and NPK fertilizer 16.16.16 1.55 grams/polybag (G2). The main effect of oil palm leaf compost was significant on all observation parameters. The best treatment is a dose of 45 grams/polybag (K3). The main effect of the dose of NPK fertilizer 16.16.16 was significant on all observation parameters. The best treatment is a dose of 1.55 grams/polybag (G2).